Ethics, Research and Vulnerable People - Berankova, Anna (Civilia, 2012)
The author of the paper Ethics, research and vulnerable people calls attention to several ethical aspects of qualitative research conducted with vulnerable people in social sciences. Research with people with cognitive deficit (for example with intellectual disabilities or dementia) is emphasised. The author draws upon her experience with research she conducted at Charles University, Prague, and University of Stirling, Scotland. Praxis of protecting the vulnerable people, gaining informed consent and proxy consent is being discussed.
Keywords: Ethics; Informed consent; People with disabilities; Qualitative research